An insight on risk management in industry by Dr. Hari - Mohd Raizalhilmy, Mohd Rais (2017)
More than 500 students participated in Industrial Talk by CEO program with Dr. Hari Narayanan, Managing Director at Motorola Solutions Malaysia Sdn. Bhd. This talk was organized by Faculty of Industrial Management and Faculty of Computer Systems & Software Engineering collaborated with Industry Partnership & Community Relation Office (JJIM).